2020
DOI: 10.31004/abdidas.v1i3.33
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Pencegahan Penularan COVID-19 Pada Anak Usia Dini Melalui Media Pembelajaran Audio Visual

Abstract: Pandemi COVID-19 yang merebak di seluruh dunia telah membuat banyak perubahan terjadi pada seluruh organisme di dalam kota, termasuk anak-anak yang merupakan golongan rentan terpapar dan tertular COVID-19. Protokol kesehatan secara cepat diterapkan untuk memutus rangkai penyebaran COVID-19 seperti kampanye kesehatan, penggunaan atribut pelindung, serta pembelajaran jarak jauh yang secara mendadak harus diterapkan pada setiap sekolah. Hal tersebut membuat banyak lembaga penyelenggara pendidikan kewalahan dalam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
0
4
0
16
Order By: Relevance
“…A better level of knowledge is a protective factor against insecurity in the face of COVID-19. A study by Wardhani et al (2020) also showed an increase in knowledge about maintaining personal hygiene through washing hands in daily life to prevent the transmission of COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
“…A better level of knowledge is a protective factor against insecurity in the face of COVID-19. A study by Wardhani et al (2020) also showed an increase in knowledge about maintaining personal hygiene through washing hands in daily life to prevent the transmission of COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Wardhani et al [14], who developed an audio-visual learning media as a medium to educate children in implementing health protocols, said that the media was expected to provide knowledge and increase children's sensitivity in maintaining personal hygiene and being aware of the dangers of coronavirus transmission. Solichah and Fadhilah [15] socialized health protocols using coloring activities in early childhood using the media "Damar Kurung".…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other researches about teachers mostly focused on strategies to prevent the infection on students (e.g. Wardhani et al, 2020;Anhusadar & Islamiyah, 2021;Safitri & Harun, 2021). This showed that there are still lack of researches that focused on challenges that students faced in online learning.…”
Section: Introductionmentioning
confidence: 99%